Case report; Identification of Bacteria in Catfish (Pangasius sp.) at the Palembang Fish Quarantine Station - Madyasta Rarassari; Marsela Aprilia (Airlangga University, 2024)
One of the causes of disease attacks can be caused by bacteria, two of which are Edwardsiella ictaluri and Streptococcus agalactiae which often attack catfish. One of the causes of disease attacks can be caused by bacteria, two of which are Edwardsiella ictaluri and Streptococcus agalactiae which often attack catfish. Disease attacks can be prevented as early as possible by periodically identifying certain bacteria so that it can facilitate appropriate treatment to prevent them. This activity aimed to study bacterial identification techniques in catfish (Pangasius sp.) at the Fish Quarantine Station for Quality Control and Safety of Fishery Products in Palembang. The method used in this activity is quantitative by field observation and collecting primary and secondary data. Activities carried out include the preparation of tools and materials. Media creation, test sample preparation, bacterial isolation, bacterial purification, basic tests, biochemical tests, and instrument digestion. The approach was carried out through basic tests and biochemical tests. Data analysis was presented in tabular form and discussed descriptively. Results: There were no bacteria with the characteristics of Edwardsiella ictaluri and Streptococcus agalactiae found in catfish observed from December 2022 to January 2023.